PENAMPILAN PRODUKSI TELUR BURUNG PUYUH PADA TINGKAT KEPADATAN KANDANG YANG BERBEDA - Latip Ali; Syukri I Gubali; Ellen J Saleh (Jambura Journal of Animal Science, 2019)
ABSTRACTLATIP ALI. 2019. Appearance of Quail Egg Production at Different Cage Density Levels. Under Guidance I Syukri I. Gubali and mentor II Ellen J Saleh.This study aims to determine the appearance of quail egg production at different cage density levels. This study used a completely randomized design consisting of 4 treatments and 3 replications. P1 treatment (density of 5 tails), P2 (density of 8 tails), P3 (density of 11 tails), and P4 (density of 14 tails). The parameters measured were egg production, egg weight, and ration consumption.The results showed that the treatment had no significant effect (P 0.05) on egg production, egg weight, and ration consumption.The highest yield for egg production was P1 0.86%, egg weight was P1 9.37g, ration consumption was P4 137.72 gr.